Children’s understanding of Aesop’s fables: relations to reading comprehension and theory of mind - Pelletier, Janette; Beatty, Ruth (Frontiers in Psychology, 2015)
Two studies examined children’s developing understanding of Aesop’s fables in relation to reading comprehension and to theory of mind. Study 1 included 172 children from Junior Kindergarten through Grade 6 in a school-wide examination of the relation between reading comprehension skills and understanding of Aesop’s fables told orally. Study 2 examined the relation between theory of mind and fables understanding among 186 Junior (4-year-old) and Senior (5-year-old) Kindergarten children. Study 1 results showed a developmental progression in fables understanding with children’s responses becoming increasingly decontextualized as they were able to extract the life lesson. After general vocabulary, passage comprehension predicted fables understanding. Study 2 results showed a relation between young children’s theory of mind development and their understanding of fables. After general vocabulary, second-order theory of mind predicted children’s fables understanding. Findings point to the importance of developing mental state awareness in children’s ability to judge characters’ intentions and to understand the deeper message embedded in fables.